Construyendo un imperio: la ocupación inca en Lunahuaná, valle medio de Cañete, Perú - Calongos Curotto, Manuel (2025)
Accounts about the Inca conquest of the Cañete Valley in the Spanish chronicles provide insights into the imperial presence in the region. However, archaeological evidence available to understand the dynamics of domination and control of the Inca state is still scarce. This report presents the results of a survey conducted in the middle Cañete Valley, where two main types of settlements were identified: elite residences and Inca imperial installations. Based on both, a territorial model was developed which allowed us to recognize the presence of two coexisting forms of spatial organization during the Inca occupation of the middle Cañete Valley. We propose that both systems were part of the strategy to consolidate Inca control in this region.